(untitled) (The Planet, 2024)
Introduction: Dengue virus infection is a major public health issue, particularly in tropical and subtropical regions, including Bangladesh. While liver dysfunction is a recognized complication of dengue, its prevalence and association with disease severity in pediatric patients remain underexplored, especially using the 2009 WHO dengue classification. This study aims to assess the prevalence and extent of hepatic dysfunction in pediatric dengue patients and correlate it with disease severity. Methods & Materials: This observational cross-sectional study was conducted from July to December 2023 at a tertiary care hospital in Dhaka, Bangladesh. Sixty-eight pediatric dengue patients were classified into dengue without warning signs, dengue with warning signs, and severe dengue based on the 2009 WHO classification. Liver function tests (SGOT, SGPT, ALP, and total bilirubin) were performed, and data were analyzed using IBM SPSS Statistics 30, with p-values <0.05 considered significant. Results: Among the 68 patients, 48.53% were school-aged children, with a male predominance of 61.76%, resulting in a male-to-female ratio of 1.6:1. SGOT and SGPT were elevated in 70.91% and 47.64% of cases, respectively, with significantly higher values observed in severe dengue (SGOT: 1,059.35 ± 23.15 IU/L, SGPT: 465.36 ± 19.04 IU/L). Total bilirubin elevation was most notable in severe dengue, reaching 26.47%. Liver dysfunction was significantly more pronounced in patients with shock or bleeding manifestations. Fever was universal, with diarrhea (60.29%), abdominal pain (55.88%), and vomiting (48.53%) being the most common additional symptoms. Conclusion: Dengue severity is closely associated with hepatic dysfunction, as indicated by elevated SGOT, SGPT, and total bilirubin levels. Early recognition and monitoring of liver involvement can guide timely interventions and improve outcomes in pediatric dengue patients.